Immunohistochemical expression of CD44 in oral squamous cell carcinoma in relation to histomorphological parameters and clinicopathological factors - Boxberg, Melanie; Götz, Carolin; Haidari, Selgai; Dorfner, Christiane; Jesinghaus, Moritz; Drecoll, Enken; Boskov, Marko; Wolff, Klaus D.; Weichert, Wilko; Haller, Bernhard; Kolk, Andreas (Histopathology, 2018)
Aims Oral squamous cell carcinoma (OSCC) is characterised by its variable clinical course. In addition to the routinely used TNM and Union for International Cancer Control systems, patient-specific prognostic/predictive biomarkers are needed. Promising biomarkers include the determination of the cancer stem cell compartment, which can be identified by CD44 expression (among other things). The aim of this study was to evaluate the impact of CD44 in OSCC in terms of correlation with histomorphology, especially targeting features of EMT, and its influence on patient prognosis. Methods and results A well-characterised cohort of 108 therapy-naive OSCCs with complete long-term follow-up and matched lymph node metastases were evaluated for CD44 expression by immunohistochemistry. CD44 expression was correlated with histomorphological characteristics (including tumour differentiation and tumour budding), clinicopathological parameters, and follow-up data. Overexpression of CD44 was detected in 37% of OSCCs within the tumour centre, in 39% of OSCCs at the invasive margin, and in 16% of lymph node metastases. CD44 overexpression at the invasive margin was significantly correlated with poor histopathological differentiation, and specifically with high tumour budding activity and single-cell invasion as signs of epithelial-mesenchymal transition (EMT). CD44 overexpression within the tumour core region and in lymph node metastases was identified as an independent prognostic factor for poor overall, disease-specific and disease-free survival in subsets of patients with advanced OSCC. Conclusion Our study demonstrates the association of CD44 with tumour aggressiveness and EMT, as well as the independent prognostic impact of CD44 in a subset of OSCCs, which underlines the role of tumour cell stemness as a key factor in malignant behaviour in this disease.
Gesehen am 02.12.2020